UJI EMPIRIS MODEL DELONE DAN MCLEAN TERHADAP KESUKSESAN SISTEM INFORMASI MANAJEMEN DAERAH (SIMDA) - Trisacti Wahyuni (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2011)
Regional Management Information System (SIMDA) is an application/system developed by the Financial and Development Supervisory Agency (BPKP) since 2003 to assist local governments in financial management. This application helps the local governments to implement integrated financial management, start from budgeting, accounting, administration, until reporting. Up to now, more than 230 local governments apply SIMDA. Does SIMDA have been successfully help local government to implement financial management? How to measure the success ful of implementation of SIMDA? The question will be tested from this study using the model of DeLone and McLean, which is a model to assess the success of a system. Based on the model of DeLone and McLean, I developed nine hypotheses. The study was conducted using questionnaires sent to users of SIMDA of local government in West Java, Central Java and East Java. After conducting tests on the nine hypotheses using the Structural Equation Model (SEM), in general, it can be said that the DeLone and McLean success model of information systems are empirically proven significantly in the successful implementation of SIMDA especially in the research object.